ETIOLOGICAL STUDY OF MARKEDLY ELEVATED SERUM FERRITIN LEVELS IN A TERTIARY HEALTH CARE CENTRE - Dr Sulekha Sinha; Dr Bikramaditya Mukherjee; Dr Chinmaya Dash; Mr. Monit Sundriyal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Ferritin, a store of iron in soluble nontoxic form, reflects total body iron stores. It protects the cell from iron-mediated oxidation-reduction reactions. It plays a role as an acute-phase reactant and has long-standing association with rheumatologic diseases eg. adult-onset Still's disease, systemic juvenile idiopathic arthritis and hemophagocytic lymphohistiocytosis / macrophage activation syndrome.1,2   The cause may be increased synthesis due to genetic or acquired effect usually seen in diseases like malignancies, hyperferritinemia-cataract syndrome. This may also be due to increased release from damaged cells eg. in acute myocardial infarction, liver disorders.  However, making a definitive diagnostic link between a markedly elevated serum ferritin determination and a specific diagnosis, rheumatologic or otherwise, can be challenging as the manifestations of these diseases are often protean and can easily be mistaken for other conditions such as sepsis with multiple organ failure or malignancy. 2,3